2014
DOI: 10.1017/s0033291714003018
|View full text |Cite
|
Sign up to set email alerts
|

Factorial validity, measurement equivalence and cognitive performance of the Cambridge Neuropsychological Test Automated Battery (CANTAB) between patients with first-episode psychosis and healthy volunteers

Abstract: Results of this study demonstrate that the structure of underlying cognitive abilities as measured by a selection of CANTAB tests is not the same for healthy individuals and FEP patients, with patients displaying widespread cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
(65 reference statements)
2
26
0
Order By: Relevance
“…According to previous studies (Leeson et al 2009;Dickinson et al 2011;Haring et al 2015b), cognitive performance is structurally different for FEP patients and CS. Therefore, we used CANTAB subtest scores instead of composite scores for comparing the cognitive performance of FEP patients and CS subjects, and mapping the performances onto regional brain systems.…”
Section: Computerized Neuropsychological Assessmentmentioning
confidence: 94%
“…According to previous studies (Leeson et al 2009;Dickinson et al 2011;Haring et al 2015b), cognitive performance is structurally different for FEP patients and CS. Therefore, we used CANTAB subtest scores instead of composite scores for comparing the cognitive performance of FEP patients and CS subjects, and mapping the performances onto regional brain systems.…”
Section: Computerized Neuropsychological Assessmentmentioning
confidence: 94%
“…Object-location learning (Experiment 1):Object-location learning, for example as studied using the CANTAB PAL test (Sahakian et al 1988), can be used to investigate the MATRICS domain of visual learning and memory and the CNTRICS domain of long term memory. Impairments in objectlocation paired-associates learning (PAL) have been found in chronic schizophrenia (Aubin et al 2009;Donohoe et al 2008;Haring et al 2014;Wood et al 2002) and can also be present at first onset of the disorder and may predict following clinical severity (Barnett et al 2005). Additionally, impairments on CANTAB PAL have been observed during the prodromal phase and may be present in relatives at risk of developing schizophrenia (Bartok et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is now substantial evidence for cognitive deficits in individuals with psychosis 1 2 3 , which is particularly related to their functional outcomes 4 . We previously reported that psychosis is characterized by a pervasive impairment in cognition during all stages of illness 5 .…”
mentioning
confidence: 99%